Zooplankton Sebagai Bioindikator Lingkungan Perairan: Studi Kasus Perairan Teluk Doreri Manokwari, Provinsi Papua Barat - Alfret Roni Marani; Alianto; Vera Sabariah; Tresia Sonya Tururaja; Marhan Manaf; Safar Dody (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2023)
The zooplankton ecological index which includes diversity, uniformity and dominance is one approach used to determine the condition of the aquatic environment. This study aims to determine the environmental status of the waters based on zooplankton ecological index which includes diversity, uniformity, and dominance in Doreri Bay water, Manokwari. This study was conducted in September 2020 at two 5- and 10-meter stations depth from the water's surface. Water quality measurements and water sampling were carried out at both stations thrice for 1 week. Water sampling to determine individual zooplankton used a 5 L volume Van Dorn. Temperature, salinity, and pH of the waters were measured successively using a rod-type thermometer with a 50 °C scale, a handheld refractometer RHSN-10ATC, and a pH meter of Orion A215 type. The measurement results obtained the temperature, salinity, and pH values ranging from 29.1 – 29.9 °C with an average of 29.5 °C, 30 – 35 ppt with an average of 33.2 ppt, and 7.9 – 8.3 with an average of 8.1, respectively. The diversity, uniformity, and dominance indexes ranged from 1.5 – 2.2, 0.7 – 1.0, and 0.1 – 0.4, respectively. The ecological status of Doreri Bay waters based on the diversity, uniformity, and dominance indexes show that the components of the food chain are still complete, including the producer and consumer groups and reducers. The effect of liquid waste from land activities around the bay has not disturbed the zooplankton.